International teacher education promising pedagogies. (Part B) - Craig, Cheryl J.; Orland-Barak, Lily (Emerald, 2015)
All countries in the world understand that education is vital to human and economic prosperity and that teacher education unavoidably is implicated. But the snag is this: political forces shaping public opinion in individual nations (particularly the U.S.) are deeply divided concerning how teacher education should proceed. This book acknowledges this Achilles heel tension, but does not become weighed down by it. Instead, it focuses on 'the practical' (Schwab, 1969), matters that have been locally deliberated and enacted. Pedagogies are named, origins (cultural/practical/theoretical/policy roots) are traced and a live example of the pedagogy unfurling in the local setting is presented from an insiderview.
Keywords: Education -- General.; Teaching skills & techniques.; Teachers -- Training of.; Education -- Study and teaching.; elektronické knihy; electronic books